Financial Sector Development in the Middle East and North Africa. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Based on data collected on a wide range of financial sector indicators, new indices of financial development for countries in the Middle East and North Africa (MENA) are constructed, encompassing six themes: development of the monetary sector and monetary policy, banking sector development, nonbank financial development, regulation and supervision, financial openness, and institutional quality. The paper finds that the degree of financial development varies across the region. Some countries have relatively well-developed banking sectors and regulatory and supervisory regimes. However, across the region, more needs to be done to reinforce the institutional environment and promote nonbank financial sector development. Based on a subset of indicators, the MENA region is found to compare favorably with a few other regions, but it ranks far behind the industrialized countries and East Asia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet